Sequential vs. prolonged 14‐day triple therapy for Helicobacter pylori eradication: the meta‐analysis may be influenced by 'geographical weighting'. Issue 10 (2nd July 2015) - Losurdo, G.; Leandro, G.; Principi, M.; Giorgio, F.; Montenegro, L.; Sorrentino, C.; Ierardi, E.; Di Leo, A.
Summary Background Sequential therapy is a first‐line regimen obtaining satisfactory Helicobacter pylori eradication. Triple therapy prolongation improves the success rate even if a recent meta‐analysis showed satisfying results only for the 14‐day regimen. Studies from Africa and North America were unavailable in previous meta‐analyses. Aim To perform a meta‐analysis comparing sequential vs. prolonged 14‐day triple therapy with regard to 'geographic weighting' by considering subgroups analysis according to metronidazole/clarithromycin low and high resistance areas. Methods Based on PRISMA recommendations, we considered all first‐line clinical studies from 2003 to November 2014. Randomised clinical trials (RCTs) were included by a search on PubMed, MEDLINE, Science Direct, EMBASE. Data on eradication rates were expressed as ITT. Risk ratio (RR), pooled RR and 95% confidence intervals were calculated by the Mantel‐Haenszel method. Data were entered into RevMan 5.2 software (Nordic Cochrane Centre) using a random‐effects model. Results Databases identified 194 studies; seven met the inclusion criteria. Overall results showed a similar effectiveness of the two regimens considered (RR = 0.99; 95% CI = 0.94–1.05; p = 0.75). In areas with high resistance to clarithromycin, sequential was superior to 14‐day triple therapy (RR = 0.95; 95% CI = 0.90–1.00; p = 0.03). In areas with high metronidazole resistance, sequential and 14‐day triple therapy were equivalent (RR = 0.99; 95% CI = 0.91–1.08; p = 0.82). Conclusions 'Geographic weighting' could be the main factor affecting the lack of differences between sequential and 14‐day triple therapy outcomes.